2010
DOI: 10.1007/s12160-010-9238-9
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Weight Discrimination Amplifies the Link Between Central Adiposity and Nondiabetic Glycemic Control (HbA1c)

Abstract: Background While the preclinical development of type 2 diabetes is partly explained by obesity and central adiposity, psychosocial research has shown that chronic stressors such as discrimination have health consequences as well. Purpose We investigated the extent to which the well-established effects of obesity and central adiposity on nondiabetic glycemic control (indexed by HbA1c) were moderated by a targeted psychosocial stressor linked to weight: perceived weight discrimination. Methods Data came from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 59 publications
5
66
2
Order By: Relevance
“…In MIDUS, Tsenkova and others [24] noted that experiencing weight discrimination amplified the adverse effects of elevated WHR on HbA1c. Among community-dwelling adults with diabetes, researchers found that participants experienced worse glycemic outcomes if they had experienced weight-based discrimination [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In MIDUS, Tsenkova and others [24] noted that experiencing weight discrimination amplified the adverse effects of elevated WHR on HbA1c. Among community-dwelling adults with diabetes, researchers found that participants experienced worse glycemic outcomes if they had experienced weight-based discrimination [11].…”
Section: Discussionmentioning
confidence: 99%
“…Discrimination also affects chronic stress, which could subsequently promote adverse physiologic changes [3, 15, 2224]. For example, weight stigma has been associated with higher glycemic parameters [24] and C-reactive protein (CRP) [15] in large, longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these findings extended to experiences of discrimination related to physical disability, but not race or age. Additionally, within a subsample of the national Midlife in the United States survey of nondiabetic adults (N=938), weight discrimination was identified as a stressor that exacerbated the harmful effects of waist to hip ratio on glycemic control (indexed by glycated hemoglobin (HbA 1c )) [68]. The observed interaction between waist to hip ratio and weight stigmatization suggests that the psychosocial consequences of weight stigma and discrimination experienced by individuals with overweight and obesity may be sources of increased vulnerability that partly explains the manifestation of clinical diabetes.…”
Section: Physiological Stress Responsesmentioning
confidence: 99%
“…Extant research has indicated that, in addition to excess body fat, psychological factors may be associated with, and predictive of elevated insulin concentration and impaired insulin sensitivity, which themselves predict the onset of type II diabetes [2], and confer additional risk for hypertension, above and beyond the contribution of obesity [3]. For instance, weight-based stigmatization, a considerable source of psychological stress, is associated with biochemical stress [4] and has been shown to amplify the link between central adiposity and nondiabetic glycemic control among overweight adults [5]. Body dissatisfaction and weight-related concerns have also been implicated in the pathophysiology of obesity, above and beyond the effects of excess adiposity [6].…”
mentioning
confidence: 99%